أثر الابتكار المالي على التمويل الإسلامي في البنوك الإسلامية - مساعيد ربعية; لكمين ليلى (University of Eloued جامعة الوادي, 2024)
"يتناول البحث بالدراسة والتأصيل موضوع"" أثر الابتكار المالي على التمويل في البنوك الإسلامية""، وهي دراسة تهدف إلى بيان دور الابتكار التمويلي وأثره في البنوك الإسلامية من خلال تحسين وتجديد المنتجات المالية والآليات التمويلية، خاصة مع تزايد الطلب على منتجات الصيرفة الإسلامية. وقد اقتضت طبيعة الموضوع تقسيمه إلي مقدمة وفصلين رئيسيين وخاتمة. ففي المقدمة قدمنا للبحث بتمهيد موجز عن موضوع الابتكار المالي، مبينا إشكالية البحث، أسباب اختيار الموضوع، أهميته وأهداف الدراسة. ثم أعقبناه بلمحة عن الدراسات السابقة، والمنهج المتبع، مع عرض خطة البحث. أما في الفصل الأول، فقد تناولنا تحديد مصطلحات البحث، حيث تطرقنا في المبحث الأول الى ماهية الابتكار المالي، بذكر مفهوم الابتكار المالي لغة اصطلاحا، نشأة وأسباب ظهور الابتكار المالي، مبينين أنواع وخصائص الابتكار المالي ومحدداته. وفي المبحث الثاني، فقد تناولنا ماهية التمويل الإسلامي، بتحديد مفهوم التمويل الإسلامي، خصائصه وأهميته، وأهم مصادر التمويل الإسلامي، وختمنا المبحث بذكر صيغ التمويل في البنوك الإسلامية. وفي الفصل الثاني، فقد تعرضنا إلى ذكر صيغ التمويل المبتكرة وأثرها في البنوك الإسلامية، حيث ذكرنا في المبحث الأول مزايا الابتكار المالي، كما عرضنا مناهج واستراتيجيات الابتكار المالي في البنوك الإسلامية. وفي المبحث الثاني عرضنا الصيغ المبتكرة للتمويل في البنوك الإسلامية. ففي المطلب الأول قمنا بذكر الصكوك بصيغ المشاركات (المشاركة والمضاربة). واحتوى المطلب الثاني على الصكوك بصيغ العقد التجاري. وتحدث في المطلب الثالث عن الصكوك بالصيغ المشابهة للمضاربة، وختمنا البحث بحملة من النتائج المتوصل إليها والاقتراحات. "The study and statement on the theme ""The impact of financial innovation on finance in Islamic banks"" is a study aimed at: - To demonstrate the role of financial innovation in the development of the financial and banking sector, especially in Islamic banks, through the improvement and renewal of financial products, especially in the light of technological developments. The nature of the topic required that it be divided into an introduction, two main chapters and a conclusion. In the introduction, we presented the paper with a brief introduction to the topic of financial innovation, indicating that the topic of financial innovation was not the subject of the topic. The problem of research, the reasons for choosing the subject, its importance and the objectives of the study.Then we followed him with a glimpse of past studies, the approach followed, and so did the search plan. In chapter I, we dealt with the definition of terms of research, where in the first paper we looked at what financial innovation is, by mentioning the concept of financial innovation as a terminological language. Financial innovation and its determinants. In the second research, we touched on what Islamic financing is, by defining the concept of Islamic finance, its characteristics and importance, the most important sources of Islamic finance, and by concluding the chapter by mentioning the forms of financing in Islamic banks. In chapter II, we mentioned early financing formulas and their impact on Islamic banks, where in the first paper we mentioned the advantages and risks of financial innovation, as we presented the methods and strategies of financial innovation in Islamic banks. The second research was entitled Innovative Forms of Finance in Islamic Banks. In the first, we mentioned the instruments in the form of participation and speculation, and the second contained the instruments in the form of a commercial contract and the third dealt with the instruments in the form of speculative. We sealed the search with a bunch of results.And suggestions. "
Keywords: التمويل الإسلامي، الابتكار، الابتكار المالي.; Islamic finance; innovation; financial innovation.